PENGARUH DAN CARA TANAM BAWANG MERAH (Allium ascalonium L.) TERHADAP HASIL - Wartapa, Agus (Jurnal Ilmu-Ilmu Pertanian, 2017)
The research titled the Inluence and haw to plant shallot (Allium ascalonium L.) on the result was conducted on March to October 2016 in BP3K Girimulyo, Girimulyo Kulon Progo with height of 250 m on soil type vertisol. The research used randomized block design arranged in factorial consisting two treatment factors with three replications. The irst factor (P) consists of 2 levels, P0=without cutting, P1= cutting 1/3 of tuber. The second factor of how to plant shallot consist of 4 levels, (S1)=spacing 20 X 20 cm population 177.778 clumps per hectar, (S2)= planting jajar lewogo 2:1 spacing 20 X 20 cm population 271.111 clumps per hectar, (S3) spacing 20 X 15 cm population 231.111 clumps per hectar, (S4)= planting jajar lewogo 2:1 spacing 20 X 15 cm population 351.111 clumps per hectar. The result showed there is interaction of second treatment to parameter of wet bulb weight per clumps highest (71.26 gram), parameter diameter of dry tuber treatment P1S1, P2S1 highest (19.65 mm, 19.95 mm). Conclusions of this study are: 1. On how to plant, cutting 1/3 of tuber tip gives good result to most of observation parameters; 2. The Tajarwo 2:1 system is better than the conventional system (non tajarwo) to shallot yield per plot of size 4,6 m2 parameter; 3. the Conventional system can increase the diameter of the shallot bulbs.